Republic of Kazakhstan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues Paper evaluates Kazakhstan's oil rules, current fiscal stance, and long-term sustainability. The sharp and sustained drop in oil prices since 2014 has reduced the value of Kazakhstan's oil wealth. Kazakhstan's non-oil deficit path has been higher than suggested by long-term benchmarks, and adjustment is needed in the coming years to avoid fiscal sustainability risks and to promote intergenerational equity. Price-based fiscal rules can help anchor short- and medium-term fiscal policy. The non-oil deficit path introduced in the new National Fund of the Republic of Kazakhstan concept is broadly consistent with the proposed approach and should be followed by timely and decisive implementation of revenue and expenditure measures.